Formation of hollow silica nanospheres by reverse microemulsion1. Issue 21 (7th June 2015) - Lin, Cheng-Han; Chang, Jen-Hsuan; Yeh, Yi-Qi; Wu, Si-Han; Liu, Yi-Hsin; Mou, Chung-Yuan
<x xml:space="preserve">Abstract</x> Formation of hollow silica nanospheres in a water-in-oil microemulsion.